Oceanic conditions in the Barrow Coastal Polynya revealed by a 10-year mooring time series. (April 2022) - Hirano, Daisuke; Fukamachi, Yasushi; Ohshima, Kay I.; Ito, Masato; Tamura, Takeshi; Simizu, Daisuke; Takatsuka, Toru; Mahoney, Andrew R.; Jones, Joshua; George, Craig; Adams, Billy; Eicken, Hajo
Highlights: A wind-driven hybrid polynya recurs annually throughout the 10-year time period. Pacific and Atlantic influences impact water mass formation in the region. Upwelled Atlantic-origin warm water also delays freeze onset in some cases. Significance of summer/autumn oceanic preconditions on winter processes. Step increase in warming after 2016, likely originating from upstream Bering inflow. Abstract: From 2009 to 2021, continuous mooring observations were conducted within the Barrow Coastal Polynya (BCP) on the northeastern Chukchi Shelf. With a 10-year mooring record (2009–2019), satellite-derived sea-ice production (SIP) data, and atmospheric reanalysis, we confirm that the BCP is a wind-driven hybrid latent and sensible heat polynya forced by northeasterly winds, and we analyze oceanic conditions and their recent changes associated with winter processes such as freeze onset, SIP, and winter-water production. The decade-long record of SIP and warm water upwelling in the BCP is dominated by interannual variability with no discernable long-term trend. In the 2015/2016 season, the SIP reached a record high for the time period studied. Water temperature and salinity prior to the freeze-up period are directly associated with SIP and winter-water production. Although wintertime SIP-related salt input is necessary, autumn salinity is, in some cases, more critical in determining winter water characteristics. The 10-year BCP mooring captures the regional changes in oceanic conditions. Summer-to-autumn ocean temperatures have been increasing as of late, especially since 2016. The prolonged presence of warmer water suggests a direct influence on freeze onset over the Chukchi Shelf and enhanced heat transport into the Arctic basin. In some cases, the upwelled Atlantic-origin warm water also delays freeze onset in the BCP. The 10-year mooring record provides evidence of recent extreme oceanic warming combined with remote and local connections from the Bering to the Chukchi Sea. This collection of data improves understanding of the impact of oceanic changes in Chukchi coastal and inner shelf waters, and regional change in the Pacific Arctic in a rapidly changing climate.